MED27 promotes melanoma growth by targeting AKT/MAPK and NF-κB/iNOS signaling pathways. Issue 1 (1st April 2016) - Tang, Ranran; Xu, Xiangdong; Yang, Wenjing; Yu, Wendan; Hou, Shuai; Xuan, Yang; Tang, Zhipeng; Zhao, Shilei; Chen, Yiming; Xiao, Xiangsheng; Huang, Wenlin; Guo, Wei; et al.
Highlights: Med27 was highly expressed in melanoma cells and tumor tissues. The silencing of Med27 led to melanoma cell proliferation inhibition, cell cycle arrest and apoptosis. The silencing of Med27 resulted in the inactivation of PI3K/AKT and MAPK/ERK signaling and the activation of Bax/Cyto C/Caspase apoptotic pathway in melanoma cells. The silencing of Med27 led to the decrease of iNOS expression through inhibiting the activation of a serial of upstream key proteins of NF-κB signaling pathway and the final translocation of p50/p65 from cytoplasm to nucleus. NF-κB and p300 interacted with Med27 and p300 mediated the acetylation of Med27 in melanoma cells. MED27 knockdown inhibited melanoma progression in vivo in a melanoma mouse model. Abstract: The inhibitors of BRAF and MEK targeting MAPK signaling pathway provide a comparatively effective therapeutic strategy for melanoma caused by BRAF mutation. However, melanoma, especially metastatic melanoma, has become one of the most threatening malignancies. Thus, the identification of exact molecular mechanisms and the key components involved in such mechanisms is urgently needed in order to provide new therapeutic options for patients with melanoma. Here, we identified MED27 as a potential melanoma target and explored its role and the associated molecular mechanism involved in melanoma progression. MED27 was found to be highly expressed in melanoma cells and tumor tissues. Its silencing led to melanoma cell proliferation inhibition, cell cycle arrest and apoptosis induction accompanied by the inactivation of PI3K/AKT and MAPK/ERK signaling and the activation of Bax/Cyto-C/Caspase-dependent apoptotic pathway. In addition, silencing of MED27 led to the decrease of iNOS expression through inhibiting the activation of a serial of upstream key proteins of NF-κB signaling pathway and the translocation of p50/p65 from cytoplasm to nucleus. MED27 was also found to be able to interact with NF-κB and p300 and to be acetylated by p300. Furthermore, the results in a xenograft tumor model indicated that melanoma progression was effectively suppressed by MED27 knockdown accompanied by the down-regulation of p-AKT, p-ERK, p-MEK1/2, MMP-9, Bcl-2 and iNOS expressions in the tumor tissues. Taken together, our study not only demonstrated the new function of MED27 as an oncogenic protein and the associated molecular mechanisms involved in melanoma progression, but also provided a possibility for the development of MED27 as a new anticancer target in melanoma therapy.